Push-pull-mooring model-based study of medical personnel’s shift intention to rural areas and the quality of public health services: a test of empirical data in Zhejiang Province - Li, Wu; Yuan, Zheng; Jiayi, Xu; Rongmian, Huo (Frontiers in Public Health, 2025)
BackgroundAiming at the current situation of shortage of medical personnel in rural areas of China, combined with the gap between primary health and preventive services and the health needs of the public, we explore the influencing factors of medical personnel’s shift intention to rural areas, and propose countermeasures to improve the quality of rural medical services and the medical security system.Subjects and methodsBased on the push-pull-mooring model, medical professionals and medical students within five prefectural-level cities (Hangzhou, Jinhua, Wenzhou, Quzhou, and Lishui) in Zhejiang Province were selected for a survey, and a model of medical personnel’s intention to shift to rural areas was established and validated using the Amos (CB-SEM), which examined the influence of healthcare resource supply, public healthcare quality, and social support on the medical personnel’s shift decision-making.FindingsThe attractiveness of alternatives significantly enhance medical personnel’s shift intention to rural areas, and the factor of personal innovation also has a positive effect on the shift intention of medical personnel, while the effect of subjective norms was not significant, and results of social factors show a negative correlation rather than the expected positive one. In contrast, dissatisfaction and shift barriers exerted pronounced negative effects. These findings provide theoretical grounding for promoting downward shift intention among healthcare talent and lay the foundation for advancing healthy lifestyles and preventive healthcare concepts in rural regions.ConclusionThis study precisely identifies the key factors influencing medical personnel’s intentions to shift, providing empirical support for optimizing rural healthcare talent retention systems, enhancing rural medical quality, and narrowing the gap in healthcare resources between urban and rural areas. It also lays a theoretical foundation for relevant policy formulation, rural health education, and improving residents’ health literacy.